Does consumer religiosity matter for green banking adoption? evidence from a Muslim-majority market - Mohamed Bouteraa; Brahim Chekima; Hanudin Amin; Elhachemi Tamma; Suddin Lada; Rudy Ansar; Lim, Ming Fook (Emerald Group Publishing Limited, 2024)
Purpose A significant dilemma facing humankind in the present time is environmental degradation. To alleviate the pressure on natural resources, green banking (GB) has been acknowledged as an effective solution. However, creating consumer engagement is still challenging for banks. Hence, the purpose of this study is to investigate the influence of religiosity on GB adoption among Muslim consumers. Design/methodology/approach The deductive approach was used to explain how GB adoption is affected by the religiosity of the consumer. A total of 332 sample data were collected cross-sectionally from Islamic bank customers in the UAE. Partial least square structural equation modelling (PLS-SEM) via Smart PLS 4 was used to analyse the data. Five dimensions (i.e. ideological, ritualistic, intellectual, consequential and experimental) were used to measure religiosity which served as the independent variable. Customer intention to adopt GB represents the dependent variable. Findings The PLS-SEM results revealed that Islamic religiosity affects the adoption of GB among Muslim consumers. Indeed, their religious commitment and beliefs affect the products they intend to adopt and how they intend to do it. Originality/value To the best of the authors’ knowledge, this is a pioneering study in the investigation of Islamic religiosity and its influence on the intention to adopt GB. This is a pioneering study in the sense that it proposes a comprehensive religiosity construct using five intertwined dimensions in the literature of GB. This study offers an improved and broader insight assessment of Islamic religiosity, which would help emphasise its significance and utility for business-related decisions by developing an emotionally-driven link between GB practices and the Muslim-oriented consumer market towards increasing the latter’s engagement.